2005
DOI: 10.1111/j.1365-2818.2005.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of low‐angle boundaries by EBSD

Abstract: A method of accurately measuring misorientations by electron backscatter diffraction (EBSD), which is an extension of that proposed by Wilkinson and based on the comparison of diffraction patterns, is described. The method has been applied to linescans, and found to improve the angular resolution by a factor of more than 30. The consequent improvement in determining misorientation axes is also analysed. Small changes of orientation very close to some low-angle boundaries were investigated and found to be artef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 10 publications
4
36
0
Order By: Relevance
“…Orientation filtering of the data does help to reduce the influence of the orientation noise [57,58], but only to a limited extent. The effect of orientation noise on accurate subgrain detection is exacerbated by the fact that an apparent gradual change of orientation is often found as the electron beam is moved across boundaries of very low misorientation angle [59]. Preliminary studies show that such artificial gradients are found for boundaries with misorientation angle less than approximately 4°.…”
Section: Subgrain Reconstructionmentioning
confidence: 99%
“…Orientation filtering of the data does help to reduce the influence of the orientation noise [57,58], but only to a limited extent. The effect of orientation noise on accurate subgrain detection is exacerbated by the fact that an apparent gradual change of orientation is often found as the electron beam is moved across boundaries of very low misorientation angle [59]. Preliminary studies show that such artificial gradients are found for boundaries with misorientation angle less than approximately 4°.…”
Section: Subgrain Reconstructionmentioning
confidence: 99%
“…The EBSD pattern recorded and indexed by traditional OIM is actually an average of the information contained within the interaction volume. Using known parameters the approximate interaction volume diameter can be simulated, and has been found by various authors to be in the range of 50-100 nm for heavier metals (Fe, Ni, Cu) and 100-200 nm for lighter metals (Al, Mg) [7,8]. The concomitant spatial resolution is dependent on how precisely mixed patterns near grain boundaries can be distinguished, and is often approximated as half the interaction volume diameter [9].…”
Section: Ebsd Overviewmentioning
confidence: 98%
“…misorientation angles in the range 0-2°) is present, even for perfect crystals [32]. Real misorientations <2°c an, therefore, not be reliably resolved using the current technique [32,33].…”
Section: Intragranular Defectsmentioning
confidence: 99%